Effectiveness of Go Green Education in Early Childhood in Ecological Disaster Mitigation Efforts - Asmungi (GoAcademica Research & Publishing, 2019)
Based on data from various sources, there are currently many natural disasters (ecological disasters) in different regions in Indonesia. Environmental hazards in the form of floods, landslides, volcanic eruptions, forest fires, smog, and so forth. Ecological disasters can occur due to natural factors or due to human intervention. Environmental hazards will get worse if prevention is not done early. One way to mitigate ecological disasters is to instill the character of caring for the environment early on. The question is whether character education cares about the environment? What does this have to do with ecological disaster mitigation efforts? How do you teach character education to care for the environment from an early age? These questions become the common thread in this article. The character of caring for the situation cannot be obtained instantly but requires a long process and a relatively long time. Someone will have a caring attitude towards the environment because of the habituation that takes place continuously and continuously. Habituations that take place consistently will be firmly planted in the subconscious mind so that they will later be exposed to their actions in daily life (habits) as the character values ​​they have. A child who has the character of caring for the environment will have a positive impact on the survival of the surrounding environment. This is where the importance of efforts to prevent (mitigate) ecological disaster early on.